Tradisi Celeng Behel di Desa Soropadan, Kecamatan Pringsurat, Kabupaten Temanggung - Farida Dwi Hastuti; Sri Prastiti Kusuma Anggraeni; Sucipto Hadi Purnomo (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The Celeng Behel tradition is a form of local wisdom practiced by the people of Soropadan Village, Pringsurat District, Temanggung Regency, and is carried out through the Sadranan Kali ritual. This study aims to explain the form and function of the Celeng Behel tradition in the community’s daily life. The research uses a qualitative descriptive method with folklore and semiotic approaches. Data were collected through interviews, observations, and documentation, then analyzed to understand the cultural meanings behind the tradition. The results show that the Celeng Behel tradition has two main forms. First, it exists as oral folklore in the form of stories passed down from generation to generation. Second, it appears as a ritual practice, namely Sadranan Kali, which is held every year on the 10th of Sapar at Bendung Pondoh. The ritual includes communal prayers, the preparation of offerings, and the release of ducks into the river. These activities symbolize the community’s gratitude for the water that supports their farming and daily needs. The tradition also has important functions. It serves as a way for the community to express their hopes and concerns about nature, especially related to water and agriculture. It also strengthens social rules and cultural values that have been passed down over time. From a semiotic point of view, the symbols used in the ritual have both direct meanings and deeper cultural meanings that form shared beliefs in the community. In conclusion, the Celeng Behel tradition is not only a cultural activity, but also an important way to maintain harmony between humans, nature, and spiritual values in the life of the Soropadan community.